A inserção da química verde no curso de licenciatura em química do DQ-UFSCar: um estudo de caso - Zandonai, Dorai Periotto (2013)
The present case study focused on the development, adaptation and analysis of the introduction of Green Chemistry in an experimental course in the first year of the chemistry teacher training Degree offered by the Chemistry Department of the Federal University of São Carlos (DQ-UFSCar), São Paulo State, Brazil. Modules for experimental lessons were proposed, based on the Science-Technology-Society (STS) teaching approach, and applied during one semester in a class of 30 undergraduate s (1st Semester 2011). The proposed didactic modules began with the presentation and discussion of documentaries with emphasis on controversial socioscientific issues, followed by an experiment of investigative character. All the conceptual topics included in these modules were originally part of the course syllabus, which were associated with the procedural and attitudinal contents emphasizing environmental and green chemistry education. The research corpus consisting of students textual production (response to questionnaires and reports) and transcript interviews (focal groups). The content analysis method was employed to describe and interpret the survey data. Also, the analysis of the experimental didactic modules using a holistic metric known as Green Star (GS) was carried out. Through the analysis of the results obtained by qualitative research in this case study, the didactic proposal enabled students to understand the contents in a complex context that included socioscientific issues, considering Green Chemistry as a mandatory demand for the initial teacher training.